Occupational exposure to particulate matter in 2 Portuguese waste-sorting units - Viegas, Susana (2014)
Objectives - This study intended to characterize work environment contamination by particles in 2 waste-sorting plants. Material and Methods - Particles were measured by portable direct-reading equipment. Besides mass concentration in different sizes, data related with the number of particles concentration were also obtained. Results - Both sorting units showed the same distribution concerning the 2 exposure metrics: particulate matter 5 (PM5) and particulate matter 10 (PM10) reached the highest levels and 0.3 μm was the fraction with a higher number of particles. Unit B showed higher (p < 0.05) levels for both exposure metrics. For instance, in unit B the PM10 size is 9-fold higher than in unit A. In unit A, particulate matter values obtained in pre-sorting and in the sequential sorting cabinet were higher without ventilation working. Conclusions - Workers from both waste-sorting plants are exposed to particles. Particle counting provided additional information that is of extreme value for analyzing the health effects of particles since higher values of particles concentration were obtained in the smallest fraction.